The Impact of Parents' Intelligence Mindset on Math Anxiety of Boys and Girls and the Role of Parents' Failure Beliefs and Evaluation of Child's Math Performance as Mediators - Xie, Fang; Duan, Xiangfei; Ni, Xuelian; Li, Lina; Zhang, Libin (Frontiers in Psychology, 2022)
The present study aimed to determine whether gender difference in math anxiety is correlated with parent’s failure mindset. A total of 431 Chinese students and their parents were recruited to complete a series of questionnaires, including math anxiety, parent’s failure mindset, parent’s intelligence mindset, and parent’s evaluation on children’s mathematical performance. The results revealed the following: (1) girls had higher math anxiety than boys; (2) parent’s failure mindset affected girl’s math anxiety through parent’s intelligence mindset and parent’s evaluation on girl’s mathematical performance; (3) parent’s failure mindset had no direct or indirect effect on boy’s math anxiety. These present results suggest that interventions needs to be applied to teach parents how to correctly react to their children’s failure in mathematics.